The Influence of Word of Mouth, Complaint Handling, and Service Quality on Customer Loyalty at Salon Surya in Singaraja - Aryanti, Dewi; Rahmawati, Putu Indah; Meitriana, Made Ary (Dinasti Publisher, 2026)
Abstract: This study aims to empirically examine the effect of word of mouth, complaint handling, and service quality on customer loyalty at Salon Surya in Singaraja. This research employs a quantitative method with a cross-sectional survey technique. The population consists of customers of Salon Surya in Singaraja, with a sample of 160 respondents selected using purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. The findings indicate that word of mouth, complaint handling, and service quality have a significant effect on customer loyalty, both partially and simultaneously, with service quality emerging as the most dominant variable in enhancing customer loyalty, while word of mouth and complaint handling also contribute positively. Theoretically, this study demonstrates that these three variables play important roles in enhancing customer loyalty in the beauty service industry and enriches the existing literature by emphasizing the dominance of service quality, supported by effective complaint handling and positive word of mouth. Practically, the findings provide valuable implications for the beauty service industry, particularly for Salon Surya in Singaraja, suggesting that improving service quality should be the primary strategy to enhance customer loyalty, accompanied by effective complaint handling and the encouragement of positive word of mouth to strengthen customer relationships and improve business performance. However, this study is limited to a single research location and focuses only on three independent variables, namely word of mouth, complaint handling, and service quality.